The Influence of Corporate Growth, divided Policy, and probability on the Value of Healthcare Companies from IDX in 2021-2023 Period - Afifah Nur Aini; Anna Marina; Gita Desipradani (P3I UMSurabaya, 2025)
The purpose of this study was to determine the relationship between company growth, dividend policy and profitability on firm value. This study used secondary data as a source of information and is a form of quantitative research. This study has a population of 35 healthcare companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023 with a total sample of 13 companies’ determined using purposive sampling method. The analysis method used is Panel Data Regression Analysis, Classical Assumption Test, Partial Test (T-Test), Simultaneous Test (F-Test) and Coefficient of Determination Test (R2) using Eviews 12 software. The results showed that company growth and dividend policy had a negative and insignificant effect on firm value; thus, hypotheses H1 and H2 were rejected. Meanwhile, profitability has a significant positive effect, supporting hypothesis H3. Simultaneously, the three variables have a significant effect on firm value, so hypothesis H4 is accepted.